PENGARUH ANGGARAN, INFORMASI, BUDAYA ORGANISASI, DAN KAPASITAS INDIVIDU TERHADAP BUDGETARY SLACK PEMERINTAHAN KOTA SERANG - murdiatun, murdiatun; Hanifah, Imam Abu; Isnawati, Iis (JURNAL RISET AKUNTANSI TIRTAYASA, 2021)
This study aims to find empirical evidence about the influence of Budget, Information, Organizational Culture, Individual Capacity and Budgetary Slack. The sampling method used in this study was purposive sampling method and obtained a sample of 15 OPDs as an observation item in Serang City. This research is an empirical study using purposive sampling technique. The data were obtained by answering questionnaires that have been distributed to Echelon III and Echelon IV employees at OPD in Serang City, with the return of the questionnaire reaching 86%, namely 90 respondents, but only 94% of the questionnaires that can be tested are 85 respondents because 6% of the returned questionnaires are 5 respondents not filled in by respondents (empty). Data analysis was performed using the Structural Equation Model (SEM) with the Smart PLS (Partial Least Square) program. The results of this study indicate that the Budget Participation variable has a positive and significant effect on Budgetary Slack, the Budget Emphasis variable has a positive and significant effect on Budgetary Slack, the Asymmetry Information variable has a positive and significant effect on Budgetary Slack, the Job Relevant Information variable has a positive and significant effect on Budgetary Slack, Organizational Culture has a positive and significant effect on Budgetary Slack, the Individual Capacity variable has a positive and significant effect on Budgetary Slack.Â Keywords: Budget, Information, Organizational Culture, Individual Capacity and Budgetary Slack